2003
DOI: 10.1126/science.1091749
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Interactions at Phospholipid-Decorated Surfaces of Liquid Crystals

Abstract: The spontaneous assembly of phospholipids at planar interfaces between thermotropic liquid crystals and aqueous phases gives rise to patterned orientations of the liquid crystals that reflect the spatial and temporal organization of the phospholipids. Strong and weak specific-binding events involving proteins at these interfaces drive the reorganization of the phospholipids and trigger orientational transitions in the liquid crystals. Because these interfaces are fluid, processes involving the lateral organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
615
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 595 publications
(655 citation statements)
references
References 23 publications
20
615
1
6
Order By: Relevance
“…Past studies have demonstrated that nematic 5CB adopts an orientation at a flat interface to water that is parallel to the interface (socalled planar anchoring of the LC; Fig. 2A) (11). When an isolated microparticle was observed at this interface (crossed polars, with one polarizer aligned parallel to the far-field orientation of the LC; Fig.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Past studies have demonstrated that nematic 5CB adopts an orientation at a flat interface to water that is parallel to the interface (socalled planar anchoring of the LC; Fig. 2A) (11). When an isolated microparticle was observed at this interface (crossed polars, with one polarizer aligned parallel to the far-field orientation of the LC; Fig.…”
Section: Resultsmentioning
confidence: 88%
“…We used silica microparticles (diameters of 2.3 μm) functionalized with the silane dimethyloctadecyl [3-(trimethoxysilyl) propyl]ammonium chloride (DMOAP; Acros). Particles functionalized with DMOAP cause 5CB to assume a perpendicular orientation at the particle surface (2), and the covalent attachment of the DMOAP to the particle surface ensures that desorption of DMOAP from the particle surface (and potentially onto the LC-aqueous interface) does not take place (9,11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations